Optimalisasi Tata Kelola Teknologi Informasi Menggunakan Framework Cobit 5.0 Pada STMIK Prabumulih - Nurmayanti Nurmayanti; Widya Cholil; Linda Atika (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2021)
This research discusses the optimization of information technology governance in STMIK Prabumulih. Which aim to get the cobit 5 framework with the condition of implementation under way to increase the value of data currently indicate that 11 domains are level 2 (repeatable) manely EDM04, EDM05, APO02, APO07, APO11, BA103, BA108, DSS04, DSS05, and MEA01. The result of the current maturity level indicate that the 2 domains are level 3 Idefined) manely APO10 and BA103, in general the strategy for improving information technology governance in STMIK Prabumulih. Then the processes and activities must be applied and documented, standardized and then integrated together according to the nedds and objectives, interviews and quetionsnaives, management result adjusted to the cobit 5 domain will be used as a value between domains. The result of the calculation of the maturity level 7 informan in the process of the results of the information technology governance maturity level in STMIK Prabumulih.